ABOUT THE POSSIBILITY OF CREATING AN EFFICIENT ENERGY ANALYZER OF CHARGED PARTICLE BEAMS BASED ON AXIALLYSYMMETRIC OCTUPOLE-CYLINDRICAL FIELD - Kambarova, Zh.T.; Saulebekov, A.O.; Kopbalina, K.B.; Tussupbekova, A.K.; Saulebekova, D.A. (KU Publ., 2021)
One of the problems in creating systems for energy analysis of charged particles beams is to determine the deflecting field and calculation the shape of the deflecting electrodes. This article is devoted to the study of the possibility of creating an effective energy analyzer of charged particle beams based on multipole electrode systems. A previously unstudied type of a multipole-cylindrical field - an electrostatic axially-symmetrical octupole-cylindrical field was chosen as the deflecting field. The field is formed by using the superposition of an electrostatic cylindrical field and a circular octupole of various contributions. The family of the equipotentials of cylindrical octupoles with planes of symmetry and antisymmetry is calculated. The calculation and analysis of equipotential portraits of the electrostatic axially-symmetric octupole-cylindrical fields with different weight contributions of the cylindrical field and circular octupole are carried out.
Keywords: energy analyzer; deflecting field; octupole-cylindrical field; equipotential; equipotential portraits; multipole electrode systems